Introduction of a new technique to measure the coefficient of restitution for nanoparticles - Schöner, Christian; Rennecke, Stephan; Weber, Alfred P.; Pöschel, Thorsten (Chemie Ingenieur Technik, 2014)
A modified single-stage low pressure impactor is described to measure the coefficient of normal restitution e for nanoparticles. The device is analysed numerically using CFD, and the gas flow inside the structured impaction plate is studied. A formula for the calculation of e is derived and first measurements of e for spherical silver particles are presented together with numerical data obtained from force-based molecular dynamics simulations. Furthermore, the simulation data for e and the sticking probability are investigated in detail for the elastic, and partly for the plastic impaction regime. Particle collisions are of great importance for the modeling of fundamental processes in a wide range of interests. So far it was not possible to determine the coefficient of restitution for nanoparticles experimentally. Here, a new measurement technique is described. The results are compared to and extended by a numerical study for detailed analysis. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Coefficient of restitution; Impaction; Molecular dynamics; Nanoparticle; Product design; Rebound

Orientation dependent properties of nanoparticle impact - Schöner, Christian; Pöschel, Thorsten (Physical Review E, 2018)
The mechanical properties of nano particles cannot be reliably described by bulk material characteristics due to their atomic structure, leading to pronounced anisotropic behavior. By means of Molecular Dynamics simulations, we study the impact of 5 nm Ag-particles on an adhesive, rigid wall. We show that the main characteristics of the impact such as the coecient of normal restitution, the sticking probability, the maximal contact force, and the degree of plastic deformation of the particle depend sensitively on the angular orientation of the nano particle prior to the impact. We introduce the scalar parameter ω describing the orientation and show that the impact characteristics can be described as functions of ω.